Prion protein gene variability in Spanish goats. Inference through susceptibility to classical scrapie strains and pathogenic distribution of peripheral PrP(sc.). - Cristina Acín; Inmaculada Martín-Burriel; Eva Monleón; Jaber Lyahyai; José Luis Pitarch; Carmen Serrano; Marta Monzón; Pilar Zaragoza; Juan José Badiola (PLoS ONE, 2013)
Classical scrapie is a neurological disorder of the central nervous system (CNS) characterized by the accumulation of an abnormal, partially protease resistant prion protein (PrP(sc)) in the CNS and in some peripheral tissues in domestic small ruminants. Whereas the pathological changes and genetic susceptibility of ovine scrapie are well known, caprine scrapie has been less well studied. We report here a pathological study of 13 scrapie-affected goats diagnosed in Spain during the last 9 years. We used immunohistochemical and biochemical techniques to discriminate between classical and atypical scrapie and bovine spongiform encephalopathy (BSE). All the animals displayed PrP(sc) distribution patterns and western blot characteristics compatible with classical scrapie. In addition, we determined the complete open reading frame sequence of the PRNP in these scrapie-affected animals. The polymorphisms observed were compared with those of the herd mates (n = 665) and with the frequencies of healthy herds (n = 581) of native Spanish goats (Retinta, Pirenaica and Moncaina) and other worldwide breeds reared in Spain (Saanen, Alpine and crossbreed). In total, sixteen polymorphic sites were identified, including the known amino acid substitutions at codons G37V, G127S, M137I, I142M, H143R, R151H, R154H, R211Q, Q222K, G232W, and P240S, and new polymorphisms at codons G74D, M112T, R139S, L141F and Q215R. In addition, the known 42, 138 and 179 silent mutations were detected, and one new one is reported at codon 122. The genetic differences observed in the population studied have been attributed to breed and most of the novel polymorphic codons show frequencies lower than 5%. This work provides the first basis of polymorphic distribution of PRNP in native and worldwide goat breeds reared in Spain.